Explaining the EUA-CER Spread - Marc Gronwald; Beat Hintermann (Center for Economic Studies and ifo Institute (CESifo), 2016)
Because of a link between the EU ETS and the Kyoto Flexible Mechanisms, the emission certificates traded on these markets are in principle interchangeable assets; despite of this, a persistent price difference exists. We explain this price spread using a theoretical model that combines three features: A binding limit for the use of Kyoto offsets within the EU ETS; a disconnect between the price of offsets and their marginal cost of production due to institutional reasons; and uncertainty about future supply and demand of offsets. Our model expresses the offset price as an average of the EUA price and an offset's outside value, weighted by the probability of a binding import limit. Using a detailed dataset on expected offset supply and demand, we provide empirical support for our theory of offset price formation. In addition, we find evidence for informational frictions governing the use of offsets within the EU ETS.
Keywords: Q02; Q54; Q58; 330; EU ETS; clean development mechanism; offset demand; EUA-CER spread